Implementation of Punishment in Improving the Process of Learning the Morals at MIS Ar Ridha Medan - Nur Aisyah Siregar; Mardianto Mardianto; Akmal Walad Ahkas (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to determine that teachers do not provide punishment to children. Punishment that is not given to children is physical punishment. When students make mistakes, the teacher gives a warning and advice to students, but students do not care about it. Then the students repeat their mistakes again, so the teacher is silent and doesn't care about the student in the class. The teacher is only focused on students who want to learn and ignore students who do not want to learn. The research method used is a qualitative research method, using the phenomology approach. The results of the teacher's perception of punishment to make students not make mistakes again and to provide understanding to students that he was guilty. and the implementation of punishment in the learning process that is planned based on a decree that has been determined by the school, namely the principal and agreed by the teacher and students.